Antioxidant and antiradical properties of polyphenols in the mechanism hepatoprotective actions of preparations Maackia amurensis - Ye. V. Ratkin; V. V. Ivanov; A. V. Ratkin; V. S. Chuchalin (Бюллетень сибирской медицины)
For finding-out of a role antioxidant and antiradical properties of poly-phenols in mechanisms hepatoprotective actions of preparations from Maackia amurensis activity of preparations from ядровой wood (Macsar), an extract of cellular culture Maackia amurensis, stilbens. Antiradical properties of preparations measured on ability to cooperate with difenilpikrilgidrazilom (DPPH). It is established, that for Macsar, PKMA, monomeasured and dimeric Stilbenes is absent correlations between antiradical activity of the given preparations from a polyphenolic complex Mauck Amur in modelling system with DPPH and them hepatoprotective effect in vivo. Monomeasured and dimeric stilbenes, possessing the highest antiradical activity appreciated on their ability to restore stable radical DPPH, have not shown expressed hepatoprotective activity at a hepatites.